Management of Hrvatske vode construction projects - Dejan Dragić; Mirko Orešković (Građevinar, 2019)
Establishment of a clear and unambiguous matrix organisation, both at the level of project owners and Hrvatske vode, is a prerequisite for an efficient and stimulating relationship between functional organisations participating in a public construction project and a particular project organisation. This paper was prepared based on research conducted in 2016 and does not reflect the effects of data from 2017 and 2018.